Determinants of maternal satisfaction with focused antenatal care services rendered at public health facilities in the West Shewa Zone, Central Ethiopia: A multicentre cross-sectional study - Bekele, Gemechu Gelan; Seifu, Benyam; Roga, Ephrem Yohannes (Frontiers in Global Women's Health, 2023)
Background: Every pregnant woman and new-born have the right to receive quality care throughout the pregnancy period. It is a proven fact that Antenatal care (ANC) reduces maternal and perinatal morbidity and mortality. The government of Ethiopia also work hard to increase the coverage and the quality of ANC. However, pregnant women’s experience to the service provided is under looked as the percentage of women completed all the ANC visits is below fifty present. Therefore, this study aimed at assessing maternal satisfaction with ANC service rendered at public health facilities of West shewa zone, Ethiopia. Methods: A facility-based cross-sectional study was conducted among women who were attending ANC in public health facilities of Central Ethiopia from September 01 to October 15, 2021. A sample of 411 women was selected using systematic random sampling. The questionnaire was pretested and the data was collected electronically using CSEntry. The collected data was exported to SPSS version 22. Study participants’ characteristics were described using frequency and percentage. Bivirate and multivariate logistic regression was carried out to identify the associated factors with the satisfaction of ANC service. Result: This study revealed that 46.7% with 95% CI (41.7%-51.6%) of the women were satisfied with ANC service. Level of health institution (AOR=5.10, 95% CI: 3.33-7.75) and Place of residence (AOR=2.38, 95% CI: 1.21-4.70) were directly associated with ANC satisfaction. History of abortion (AOR=0.19, 95% CI: 0.07-0.49) and previous mode of delivery (AOR=0.30, 95% CI: 0.15-0.60) were negatively associated with women satisfaction with ANC service. Conclusion: More than half of pregnant women who attended ANC were dissatisfied with the focused antenatal care. This is alarming as it is lower than the finding of previous studies conducted in Ethiopian. Institutional variables, interactions with patients, and previous experiences of pregnant women have an impact on level of satisfaction. Due attention should be given for primarily health and communication of health professionals with pregnant women to improve the satisfaction of pregnant women with the ANC service offered.